UJI KANDUNGAN FORMALIN PADA BUAH PEPAYA (Carica papaya L.) DAN BUAH NANAS (Ananas comosus L.) YANG DI JUAL DILINGKUNGAN UIN RADEN FATAH PALEMBANG DENGAN METODE SPEKTROFOTOMETRI - Agustiani Dumeva Putri; elfira rosa pane; Vini Khasianturi (Biota, 2016)
Fruit is a natural product that has benefits such as giving nutrient for society, incoming source, pervading labor if it is afforded intensively. The purpose of this research is to measure whether there is formalin or not in papaya and pineapple which sold at UIN Raden Fatah environtment. The kind of this research uses qualitative descriptive appearance organolaptic test and colour test and experiment method appearance quantitative test by using spectrophotometer. The result of measuring organolaptic with color of parameter, taste, and tekstur surely, there is difference to fruit sample of different fruit seller. Colour test is done by using Schiff reagen. The result of Colour test shows all sample don’t contain formalin, noted with yellow liquid. Quantitative test uses spectrophotometer. The result of quantitative test shows all sample examinee identified formalin. Formalin level of each sample is different. The smallest formalin level is 0,0007 ppm at papaya in A seller and the highest is 0,0025 ppm at pineapple in A seller.